Organic photonics and electronics: University of Strathclyde, UK, [Glasgow] 8-10 September 2014 ; [a General Discussion on Organic Photonics and Electronics] - Skabara, Peter (Faraday discussions, 2014)
Spiers Memorial Lecture: Organic electronics: an organic materials perspective /Fred Wudl --Exploring coherent transport through [pi]-stacked systems for molecular electronic devices /Qian Li and Gemma C. Solomon --A quantum chemical study from a molecular transport perspective: ionization and electron attachment energies for species often used to fabricate single-molecule junctions /Ioan Båldea --Breaking the simple proportionality between molecular conductances and charge transfer rates /Ravindra Venkatramani, Emil Wierzbinski, David H. Waldeck and David N. Beratan --Molecular diodes enabled by quantum interference /Arunabh Batra [and 6 others] --Measurement and control of detailed electronic properties in a single molecule break junction /Kun Want, Joseph Hamill, Jianfeng Zhou, Cunlan Guo and Bingqian Xu --A computational study of potential molecular switches that exploit Baird's rule on excited-state aromaticity and antiaromaticity /H. Löfrås [and 6 others] --Organic semiconductor distributed feedback laser pixels for lab-on-a-chip applications fabricated by laser-assisted replication /Xin Liu [and 10 others] --Rigid biimidazole ancillary ligands as an avenue to bright deep blue cationic iridium(III) complexes /Adam F. Henwood, Sloane Evariste, Alexandra M. Z. Slawin and Eli Zysman-Colman --Lasing of Tamm states in highly efficient organic devices based on small-molecule organic semiconductors /R. Brückner, V. G. Lyssenko, S. Hofmann and K. Leo --Dynamic amplification of light signals in photorefractive ferroelectric liquid crystalline mixtures /Takeo Sasaki, Satoshi Kajikawa and Yumiko Naka --Organic semiconducting single crystals as solid-state sensors for ionizing radiation /Beatrice Fraboni, Andrea Ciavatti, Laura Basiricò and Alessandro Fraleoni-Morgera --Parameter free calculation of the subgap density of states in poly(3-hexylthiophene) /Jarvist M. Frost, James Kirkpatrick, Thomas Kirchartz and Jenny Nelson --In situ formation of organic-inorganic hybrid nanostructures for photovoltaic applications /Sebastian Wood [and 5 others] --Computational investigation of hole mobilities in organic semiconductors: comparison of single crystal structures and surface adsorbed clusters /Rose A. Krawczuk, Steven Tierney, William Mitchell and Joseph J. W. McDouall --Supramolecular control of organic p/n-heterojunctions by complementary hydrogen bonding /Hayden T. Black, Huaping Lin, Francine Bélanger-Gariépy and Dmitrii F. Perepichka --Design of donor-acceptor star-shaped oligomers for efficient solution-processible organic photovoltaics /S. A. Ponomarenko [and 8 others] --Novel electrochemiluminescent materials for sensor applications /Lynn Dennany, Zahera Mohsan, Alexander L. Kanibolotsky and Peter J. Skabara --Hybrid organic semiconductor lasers for bio-molecular sensing /Anne-Marie Haughey [and 7 others] --Bio-sorbable, liquid electrolyte gated thin-film transistor based on a solution-processed zinc oxide layer /Mandeep Singh [and 10 others] --Characterization and simulation of electrolyte-gated organic field-effect transistors /Katharina Melzer [and 5 others] --Organic electronics and photonics: concluding remarks /Donal D. C. Bradley --Poster titles --List of participants.
"A general discussion on organic photonics and electronics was held in Glasgow, UK on the 8th, 9th and 10th of September 2014."
Includes bibliographical references
Keywords: Konferenzschrift; Elektrolumineszenz; Organischer Halbleiter